Diabetic nephropathy associates with deregulation of enzymes involved in kidney sulphur metabolism. Issue 20 (16th September 2020) - Uyy, Elena; Suica, Viorel Iulian; Boteanu, Raluca Maria; Safciuc, Florentina; Cerveanu‐Hogas, Aurel; Ivan, Luminita; Stavaru, Crina; Simionescu, Maya; Antohe, Felicia
Abstract: Nephropathy is a major chronic complication of diabetes. A crucial role in renal pathophysiology is played by hydrogen sulphide (H2 S) that is produced excessively by the kidney; however, the data regarding H2 S bioavailability are inconsistent. We hypothesize that early type 1 diabetes (T1D) increases H2 S production by a mechanism involving hyperglycaemia‐induced alterations in sulphur metabolism. Plasma and kidney tissue collected from T1D double transgenic mice were subjected to mass spectrometry‐based proteomic analysis, and the results were validated by immunological and gene expression assays.T1D mice exhibited a high concentration of H2 S in the plasma and kidney tissue and histological, showed signs of subtle kidney fibrosis, characteristic for early renal disease. The shotgun proteomic analyses disclosed that the level of enzymes implicated in sulphate activation modulators, H2 S‐oxidation and H2 S‐production were significantly affected (ie 6 up‐regulated and 4 down‐regulated). Gene expression results corroborated well with the proteomic data. Dysregulation of H2 S enzymes underly the changes occurring in H2 S production, which in turn could play a key role in the initiation of renal disease. The new findings lead to a novel target in the therapy of diabetic nephropathy. Mass spectrometry data are available via ProteomeXchange with identifier PXD018053.